Tedd and Huggly - Canizares, Susan (New York : Scholastic, 1999)
Examines the daily activities of author-illustrator Tedd Arnold and his creation Huggly, a little monster.
Keywords: Arnold, Tedd -- Juvenile literature; Author's American -- 20th century -- Biography -- Juvenile literature